Reconsidering the Limits to Growth A Report to the Russian Association of the Club of Rome - Sadovnichy, Viktor; Akaev, Askar; Ilyin, Ilya.; Malkov, Sergey; Grinin, Leonid; Korotayev, Andrey (Cham : Springer International Publishing : Imprint: Springer, 2023)
Echoing the famous "The Limits to Growth" report from 1972, this edited volume analyses the changes that the World System has undergone to the present, on the fiftieth anniversary of the original report. During the past fifty years, both the concept and understanding of these limits have significantly changed. This book highlights that the evolution of the World System has approached a new critical milestone, moving into a fundamentally new phase of historical development, when the old economic and social technologies no longer work as efficiently as before or even begin to function counterproductively, which leads the World System into a systemic crisis. The book discusses the transition of human society to a new phase state, the shape of which has not yet been determined. New approaches are needed for both, for the analysis of the global situation, and for forecasts. The book is based on an integrated approach including the world-systems, historical and evolutionary perspectives, as well as a systematic view of society, in which changes in one subsystem cause transformations in others. Through mathematical modeling, it defines the main vectors of transformations of the World System; makes a detailed forecast of the development of all the main subsystems of the society and the World System, while presenting horizons of changes from short-term to ultra-long-term; and presents different development scenarios as well as recommendations on how to achieve a transition to the most favorable scenario. The book will appeal to members and followers of the Club of Rome, policy-makers, as well as to scholars from various disciplines interested in a better understanding of the World System evolution, global futures, development studies, climate change, and future societies. .
Chapter 1. Introduction: Hoping for the Future -- Part 1: Looking into the Past and the Future -- Chapter 2. Macrohistorical Approach -- Chapter 3. Future Society and Transition to It -- Part 2: Problems, Forecasts, Solutions (Climate, Ecology, Demography, Aging) -- Chapter 4. Climate and Energy: Scenarios of Energy Transition and Global Temperature Changes Based on Current Technologies and Trends -- Chapter 5. Ecology: Life in the "Unstable Biosphere" -- Chapter 6. Demography: Toward Optimization of Demographic Processes -- Chapter 7. Global Aging - an Integral Problem of the Future: How to Turn a Problem into a Development Driver? -- Part 3: Problems, Forecasts, Solutions (Technology, Economics, Socio-Political Development) -- Chapter 8. Technology: Limitless Possibilities, Effective Control -- Chapter 9. Economics: Optimizing Growth -- Chapter 10. Socio-Political Transformations: A Difficult Path to Cybernetic Society -- Chapter 11. Future Political Change: Toward a More Efficient World Order -- Chapter 12. High Income and Low Income Countries: Toward a Common Goal at Different Speeds -- Chapter 13. Africa - the Continent of the Future: Challenges and Opportunities -- Part 4: Modeling Social Self-Organization and Historical Dynamics -from Agrarian to Cybernetic W-Society -- Chapter 14. Modeling Social Self-Organization and Historical Dynamics: An Overview -- Chapter 15. Modeling Social Self-Organization and Historical Dynamics: A General Approach -- Chapter 16. Modeling Social Self-Organization and Historical Dynamics: Agrarian Society -- Chapter 17. Modeling Social Self-Organization and Historical Dynamics: Industrial Society -- Chapter 18. Modeling Social Self-Organization and Historical Dynamics: Global Phase Transitions -- Chapter 19. Modeling Social Self-Organization and Historical Dynamics: Modern Society and a Look into the Global Futures: Cybernetic W-Society -- Chapter 20. Modeling Social Self-Organization and Historical Dynamics: Africa's Futures -- Chapter 21. Analyzing Social Self-Organization and Historical Dynamics: Future Cybernetic W-Society: Socio-Political Aspects -- Chapter 22. Analyzing Social Self-Organization and Historical Dynamics: Life Quality Index -- Chapter 23. Conclusion: Reconsidering The Limits - Suggestions (Come On!).
Keywords: Economic development; Globalization; Sustainability; Bioclimatology; Population -- Economic aspects; Economic Growth; Globalization; Sustainability; Development Studies; Climate Change Ecology; Population Economics